Ehegesundheit: Überblick über die Entwicklungen anhand der Gesetzgebung im „Dritten Reich" und internationale Dimensionen - Abram, Helen Ahlke (Díké - A Márkus Dezső Összehasonlító Jogtörténeti Kutatócsoport folyóirata, 2020)
The following article traces the development of the marital law legislation in the Third Reich, that governed the fostering of „fit“ families with large numbers of children through economic measures and established marriage restrictions for the „inferior“ population. By implementing these regulations, the legislation aimed to enable early „fit“ marriages and large families and also prevent the reproduction of the „inferior“ in order to strengthen the racial corpus. After portraying the essential legal framework in early 20th century Germany, the article finally summarises the international dimensions of this subject matter and focuses on the legislation in Hungary. Considering this, the article shows, that the idea of eugenics respectively racial hygiene was impacting the population policy and therewith the legislation globally. In comparison, the German legislation of this scope has nonetheless been the most comprising and radical one during the period of 1920–1945.